Well-Being in Highly Hypnotizable Persons. Issue 2 (3rd April 2022) - Biscuola, Edith; Bongini, Marianna; Belcari, Iacopo; Santarcangelo, Enrica L.; Sebastiani, Laura
ABSTRACT: Both hypnotizability and well-being are relevant to health. This study aimed to investigate whether high hypnotizability was positively associated with well-being and whether the latter was related to the activity of the behavioral inhibition/approach system (BIS/BAS). ANOVA revealed significantly higher scores on the General Well-Being Index (PGWBI) in highly hypnotizable (highs, n = 31) compared with low hypnotizable participants (lows, n = 53), with medium hypnotizable participants (mediums, n = 41) exhibiting intermediate values. This finding was discussed in relation to other hypnotizability-related traits, such as morpho-functional brain characteristics, equivalence between imagery and perception, and interoceptive sensitivity. A secondary finding was a nonsignificant gender difference in scores on the PGWBI. The highs' higher well-being could be considered a favorable prognostic factor for physical and mental health.